(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In the article, firstly, general information about the analysis of the literature on increasing the role of monetary instruments in the regulation of the economy by the state is given. Then, how the history of issues of increasing the role of monetary instruments in the regulation of the economy by the state began. At the same time, the essence of monetary policy and issues of increasing the role of monetary instruments in the regulation of the economy by the state, as well as conclusions on effective solutions, are focused on.